Research progress in the application of in situ hydrogel system in tumor treatment - Weipeng Wei; Hongfang Li; Chengchen Yin; Fushan Tang (Taylor & Francis Group, 2020)
The in situ hydrogel drug delivery system is a hot research topic in recent years. Combining both properties of hydrogel and solution, in situ hydrogels can provide many advantages for drug delivery application, including easy application, high local drug concentration, prolonged drug retention time, reduced drug dose in vivo, good biocompatibility and improved patient compliance, thus has potential in tumor treatment. In this paper, the related literature reports in recent years were reviewed to summarize and discuss the research progress and development prospects in the application of in situ hydrogels in tumor treatment.